Age, Growth and Length-weight Relations of Common Sole (Solea solea Linnaeus, 1758) from Southern Aegean Sea - Hasan Cerim; Celal Ateş (Aquatic Sciences and Engineering)
In this study, age and sex compositions, length distributions, growth parameters and length-weight relationships of common sole populations were determined in Güllük Bay, southern Aegean Sea, Turkey. Trammel nets and beach seines which have different full mesh sizes were used to obtain samples. Sex ratio (female:male) was found to be 1.14:1. Growth parameters of the common sole in Güllük Bay was described as; L∞=33.95, K=0.208 y-1, t0=-0.032, L∞=31.98, K=0.236 y-1, t0=-0.037 y and L∞=29.11, K=0.324 y-1, t0=-0.030 y, for sexes combined, females and males, respectively. Lengthweight relationships for combined sexes, females and males were W=0.0079L3.064, W=0.0072L3.101 and W=0.0088L3.024, respectively. Combined individuals and females showed positive allometric growth and males showed isometric growth. Ages ranged between 0-9 years. Study results could be useful for further common sole fishery management strategies.